NEUROEDUCACIÓN Y SU INFLUENCIA EN EL APRENDIZAJE EN LOS ESTUDIANTES DE 2DO AÑO EGB UNIDAD EDUCATIVA 5 DE JUNIO DE LA PARROQUIA ISLA DE BEJUCAL - CEDEÑO QUINTO LEONELA (2024)
Neuroeducation is a discipline that aims to combine contributions from neuroscience, psychology, cognitive science and education and focuses on understanding how the brain learns and uses this information to develop methods that can be more effective in guiding proposals for new curricula and new educational policies. The present research project called Neuroeducation and its influence on learning in 2nd year EGB students of the 5 de Junio Educational Unit of the Isla de Bejucal parish has the general objective of determining the influence of Neuroeducation on learning in students of 2nd year EGB June 5 Educational Unit of the Isla de Bejucal parish. In this study, a descriptive methodological approach was used where the influence of Neuroeducation on student learning was detailed and at the same time a detailed and comprehensive vision of how the integration of neuro-educational principles impacts the educational process was established. The study focused on describing the specific pedagogical practices that incorporate Neuroeducation, evaluating how these strategies impact key aspects of learning, such as motivation, attention, information retention and academic performance. In addition, the perceptions of teachers and students about the effectiveness of these practices in the educational process were analyzed. Documentary research was used to develop the theoretical framework, which focused on analyzing and synthesizing information from relevant documentary sources related to Neuroeducation.